1997
DOI: 10.1101/gr.7.4.389
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping PCR for Bidirectional PCR Amplification of Specific Alleles: A Rapid One-Tube Method for Simultaneously Differentiating Homozygotes and Heterozygotes

Abstract: Rapid detection of single-base changes is fundamental to molecular medicine. PASA (PCR amplification ofspecific alleles) is a rapid method of genotyping single-base changes, but one reaction is required for each allele. Bidirectional PASA (Bi-PASA) was developed to distinguish between homozygotes and heterozygotes in one PCR reaction by utilizing novel primer design with appropriate cycling conditions. In Bi-PASA, one of the alleles is amplified by a PASA reaction in one direction while the second allele is am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 13 publications
1
100
0
Order By: Relevance
“…Genomic DNA was extracted from peripheral blood leukocytes by a salting-out procedure (Miller et al 1988). The homozygosity for the SCD mutation was confirmed by a bidirectional allele-specific polymerase chain reaction (PCR) as described (Liu et al 1997). The number of (TA) repeats in the UGT1A1 promoter was analysed by a PCR-based methodology using the primers described by Monaghan et al (1996) in which the sense primer was 5-carboxyfluorescein (FAM) fluorescent-tagged.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood leukocytes by a salting-out procedure (Miller et al 1988). The homozygosity for the SCD mutation was confirmed by a bidirectional allele-specific polymerase chain reaction (PCR) as described (Liu et al 1997). The number of (TA) repeats in the UGT1A1 promoter was analysed by a PCR-based methodology using the primers described by Monaghan et al (1996) in which the sense primer was 5-carboxyfluorescein (FAM) fluorescent-tagged.…”
Section: Methodsmentioning
confidence: 99%
“…1). Primers for Bi-PASA were designed following the guidelines proposed by Liu et al [26], taking into account both the melting temperature of both the primers and the largest PCR segment (PQ). The primers used in this study are shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…However, most of the genotyping techniques currently available are still either time-consuming and laborious or require expensive equipment [23][24][25]. In this sense, we adapted a simple and rapid method, allowing genotype determination in a single reaction based in the bidirectional PCR amplification of specific alleles (Bi-PASA) [26] in both the TLR4 (Asp299Gly, Thr399Ile) and TLR9 (T-1237C) genes, a methodology amenable to large scale analysis, using technology available in most scientific laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Allelic variants were genotyped using bidirectional PCR amplification of specific alleles, as previously described. 31,32 Regarding quality control, each PCR set comprised randomly selected replicates of previously typed samples from the study and two negative controls. Agreement for quality control and duplicates was X99% for all assays.…”
Section: Genotypingmentioning
confidence: 99%